Myeloid Cells in Intact Human Cervical Explants Capture HIV and Can Transmit It to CD4 T Cells - Trifonova, Radiana T.; Bollman, Brooke; Barteneva, Natasha S.; Lieberman, Judy (Frontiers in Immunology, 2018)
The importance of myeloid cells in HIV transmission in the female genital tract is uncertain. Because it is difficult to study the early events in HIV transmission in humans, most of our knowledge is based on animal models of SIV infection in Rhesus macaques and more recently HIV infection in humanized mice. However, these models may not accurately recapitulate transmission in the human genital tract. CD14+ myeloid cells are the most abundant hematopoietic cells in the human cervical mucosa, comprising 40-50% of CD45+ mononuclear cells. Most CD14+ cells are CD14+CD11c- macrophages and about a third are CD14+CD11c+ tissue dendritic cells, which express the HIV-binding receptors, DC-SIGN and CX3CR1. To examine the role of mucosal myeloid cells in HIV transmission, we infected intact healthy human cervical explants with CCR5-tropic HIV-1 ex vivo and then sorted populations of cervical immune cells 20 hours later to determine whether they took up virus and could transmit it to activated CD4 T cells. Viral RNA was detected in CD14+ myeloid cells in all but one of ten donor tissue samples, even when HIV RNA was not detected in CD4+ T cells. HIV RNA was detected predominantly in CD14+CD11c+ dendritic cells rather than in CD14+CD11c- macrophages. The reverse transcriptase inhibitor, nevirapine, reduced HIV RNA in CD4+ T cells, but not in CD14+ cells. Moreover, integrated HIV DNA were not detected above background in myeloid cells but was detected in T cells. These data suggest that although HIV replicates in T cells, myeloid cells in the female genital mucosa capture viral particles, but do not replicate the virus at early timepoints. However, sorted CD14+ myeloid cells isolated 20 hours post-infection from 5 HIV-infected cervical explants tested all transmitted HIV to activated CD4+ T cells, while only 1 sample of sorted CD4+ T cells did. Thus, myeloid cells in human cervical tissue capture HIV and are an important early cellular storage site of infectious virus.